Effect of Helicobacter pylori-Associated Chronic Gastritis on Autonomous Activity and Sleep Quality in Mice - Liu, Haihua; Zheng, Wenlong; Zhang, Ling; Lin, Tangtang; Tang, Yang; Hu, Ling (Frontiers in Pharmacology, 2022)
Many reports have shown that patients with Hp-associated chronic gastritis exhibit anxiety and poor sleep quality. However, less is known about the effects and specific manifestations of Hp-associated chronic gastritis on autonomous activity and sleep quality in animals. Here, we investigated the effect of Helicobacter pylori (Hp)-associated chronic gastritis on autonomous activity and sleep quality in mice. To do this, a Hp-associated chronic gastritis mouse model was first established, then analyzed for autonomous activity, relative to controls, for 15 minutes using an autonomous activity tester. Next, sleep quality of mice was detected by sodium pentobarbital-induced sleep experiment and results compared between groups. The results showed that male mice in the model group exhibited higher activity counts but lower forelimb lift counts, relative to those in the control group, although there were no significant differences (all P > 0.05). Conversely, female mice in the model group recorded lower activity counts, albeit at no significant difference (P > 0.05), and significantly lower counts of forelimb lift (P < 0.05), relative to those in the control group. Notably, male mice in the model group had longer sleep latency and shorter sleep duration than those in the control group, albeit at no significant differences (all P > 0.05). On the other hand, female mice in the model group recorded significantly longer sleep latency as well as longer sleep duration compared to those in the control group (all P < 0.01). We conclude that Hp-associated chronic gastritis exerts certain effects on autonomous activity and sleep quality of mice in a gender-dependent manner. Notably, female mice with Hp-associated chronic gastritis had lower activity and forelimb lift counts, as well as prolonged sleep latency, and shortened sleep duration. These effects were all statistically significant except for activity counts.